Regulatory Immune Mechanisms in Tolerance to Food Allergy - Satitsuksanoa, Pattraporn; Jansen, Kirstin; Głobińska, Anna; van de Veen, Willem; Akdis, Mübeccel (Frontiers in Immunology, 2018)
Oral tolerance can develop after frequent exposure to food allergens. Upon ingestion, food is digested into small protein fragments in the gastrointestinal tract. Small food particles are later absorbed into the human body. Interestingly, some of these ingested food proteins can cause allergic immune responses, which can lead to food allergy. So far it has not been completely elucidated how these proteins become immunogenic and cause food allergies. In contrast, oral tolerance helps to prevent the pathologic reactions against different types of food antigens from animal or plant origin. Tolerance to food is mainly acquired by dendritic cells, epithelial cells in the gut, and the gut microbiome. A subset of CD103+ DCs is capable of inducing T regulatory cells (Treg cells) that express anti-inflammatory cytokines. Anergic T cells also contribute to oral tolerance, by reducing the number of effector cells. Similar to Treg cells, B regulatory cells (Breg cells) suppress effector T cells and contribute to the immune tolerance to food allergens. Furthermore, the human microbiome is an essential mediator in the induction of oral tolerance or food allergy. In this review, we outline the current understanding of regulatory immune mechanisms in oral tolerance. The biological changes reflecting early consequences of immune stimulation with food allergens should provide useful information for the development of novel therapeutic treatments.